Ni(OH)2 microspheres in situ self-grown on ultra-thin layered g-C3N4 as a heterojunction electrocatalyst for oxygen evolution reaction. (20th December 2021) - Li, Tong; Ma, Xinxia; Wu, Jiang; Chu, Fenghong; Qiao, Lingxia; Song, Yubao; Wu, Maoliang; Lin, Jia; Peng, Lin; Chen, Zhongwei
Abstract: Oxygen evolution reaction (OER), as a part reaction of the overall water splitting, is deemed as a prospective technology for large-scale energy storage. However, the sluggish kinetics (large overpotential) and the expensive cost of noble metal-based electrocatalysts (RuO2 and IrO2 ) restrain the widespread usage of OER. Hence, the discovery of non-precious metal-based electrocatalysts with tiny overpotential, satisfactory current density and outstanding stability has become urgent. In this work, we have prepared ultra-thin layered g-C3 N4 by a two-step thermal peeling method and synthesized Ni(OH)2 /g-C3 N4 composite by a simple one-step solvothermal method. Benefiting from the layered g-C3 N4 as substrate, the overpotential of Ni(OH)2 /g-C3 N4 composite was just 240 mV at 10 mA cm −2, which gives an unexpected improvement in the electrochemical performance of the composite samples compared to pure Ni(OH)2 ( η = 460 mV). Additionally, the formation of heterojunction effectively reduces the resistance to electron transport in OER, the resistance of Ni(OH)2 /g-C3 N4 ( Rct = 38.8 Ω) is far smaller than those of bare Ni(OH)2 ( Rct = 41.6 Ω) and layered g-C3 N4 ( Rct = 43.6 Ω) at the open circuit potential. Ni(OH)2 /g-C3 N4 composite samples display outstanding electrochemical stability, maintaining 85% of initial current density for 12 h. Moreover, density functional theory (DFT) demonstrates that Δ G 3 of Ni(OH)2 /g-C3 N4 composite ( η = 0.46 V) is much lower than that of bare Ni(OH)2 ( η = 0.64 V). These undeniable results demonstrate that Ni(OH)2 /g-C3 N4 composite materials is promising alternative materials to replace precious metal-based OER electrocatalysts in the field of water splitting. Graphical abstract: Image, graphical abstract